Willingness to pay for sustainable hospitality : the case of Portugal - Antunes, Beatriz Ribeiro Mendes (2021)
The main goal of this dissertation is to assess what factors have impact on the willingness to pay for a hotel with sustainable practices, in Portugal. This is an important topic to analyze since tourism is so important for the global economy and the increasingly need of a more sustainable tourism practice worldwide. However, it is important to have a segmentation on which behavior to expect from the customer. To do this, demographics, travelling habits, attitudes towards green lodging, price consciousness on hospitality industry and whether or not people were environmentally friendly, were considered to be the best predictors of what would make the willingness to pay fluctuate for the portuguese client. The main finding was that the variables Attitudes and Client profile (gender and pro-environmental) do have a significant impact on the willingness to pay more towards green and sustainable practices on the hotel industry. Although it was previously thought that travelling habits and price sensitivity would also have impact due to previous literature, that was not true for the sample in study and it describes the behaviour of the portuguese client.